(3GSJjYGH GdhLhg GdeecfI aj UfYI GdGSWQdGHs - (3GHf GdeJbfI , CHh YHO Gddg eMeO Hf Ydj Hf eMeO Hf GdMSf GdQMHj,J (B577 (3g` s
(3ChdgG (B:s
(3GdCfaS GdUGajI PhGJ fRGY hGTJbGb Edi JUhQGdehLhOGJ hGdEMGWI HgG HEWdGb s
(3BNQgG (B:s
(3de jJTcd ajg EdG eeG eQGcRgG HjfI hHjf hEf LYd bWH GdJSWjM fbWI s
(3HChdg Jedcs
(3Hg LOGhd adcjIs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B279 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B47s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdadcs